AtTCTP2, an Arabidopsis thaliana homolog of Translationally Controlled Tumor Protein, enhances in vitro plant regeneration - Toscano-Morales, Roberto; Xoconostle-Cázares, Beatriz; Cabrera-Ponce, José Luis; Hinojosa-Moya, Jesús; Ruiz-Salas, Jorge Luis; Galván-Gordillo, Valentin; Guevara-González, Ramon Gerardo; Ruiz-Medrano, Roberto (Frontiers in Plant Science, 2015)
The Translationally Controlled Tumor Protein (TCTP) is a central regulator of cell proliferation and differentiation in animals, and probably also in plants. Arabidopsis harbors two TCTP genes, AtTCTP1 (At3g16640), which is an important mitotic regulator, and AtTCTP2 (At3g05540), which is considered a pseudogene. Nevertheless, we have obtained evidence suggesting that this gene is functional. Indeed, a T-DNA insertion mutant, SALK_045146, displays a lethal phenotype during early rosette stage. Also, both the AtTCTP2 promoter and structural gene are functional, and heterozygous plants show delayed development. AtTCTP1 cannot compensate for the loss of AtTCTP2, since the accumulation levels of the AtTCTP1 transcript are even higher in heterozygous plants than in wild-type plants. Leaf explants transformed with Agrobacterium rhizogenes harboring AtTCTP2, but not AtTCTP1, led to whole plant regeneration with a high frequency. Insertion of a sequence present in AtTCTP1 but absent in AtTCP2 demonstrates that this suppresses the capacity for plant regeneration; also, this phenomenon requires the presence of TCTP (AtTCTP1 or 2) in the nuclei of root cells. This confirms that AtTCTP2 is not a pseudogene and suggests the involvement of certain TCTP isoforms in vegetative reproduction in some plant species.